Genetic characterization of Rhodococcus rhodochrous ATCC BAA-870 with emphasis on nitrile hydrolysing enzymes - Frederick, Joni (University of Cape Town, 2014)
Includes abstract. === Includes bibliographical references. === Rhodococcus rhodochrous ATCC BAA-870 (BAA-870) had previously been isolated on selective media for enrichment of nitrile hydrolysing bacteria. The organism was found to have a wide substrate range, with activity against aliphatics, aromatics, and aryl aliphatics, and enantioselectivity towards beta substituted nitriles and beta amino nitriles, compounds that have potential applications in the pharmaceutical industry. This makes R. rhodochrous ATCC BAA-870 potentially a versatile biocatalyst for the synthesis of a broad range of compounds with amide and carboxylic acid groups that can be derived from structurally related nitrile precursors. The selectivity of biocatalysts allows for high product yields and better atom economy than nonselective chemical methods of performing this reaction, such as acid or base hydrolysis. In order to apply BAA-870 as a nitrile biocatalyst and to mine the organism for biotechnological uses, the genome was sequenced using Solexa technology and an Illumina Genome Analyzer. The Solexa sequencing output data was analysed using the Solexa Data Analysis Pipeline and a total of 5,643,967 reads, 36-bp in length, were obtained providing 4,273,289 unique sequences. The genome sequence data was assembled using the software Edena, Velvet, and Staden. The best assembly data set was then annotated automatically using dCAS and BASys. Further matepaired sequencing, contracted to the company BaseClear® BV in Leiden, the Netherlands, was performed in order to improve the completeness of the data. The scaffolded Illumina and mate-paired sequences were further assembled and annotated using BASys. BAA-870 has a GC content of 65% and contains 6997 predicted protein-coding sequences (CDS). Of this, 54% encodes previously identified proteins of unknown function. The completed 5.83 Mb genome (with a sequencing coverage of 135 X) was submitted to the NCBI Genome data bank with accession number PRJNA78009. The genome sequence of R. rhodochrous ATCC BAA-870 is the seventh rhodococcal genome to be submitted to the NCBI and the first R. rhodochrous subtype to be sequenced. An analysis of the genome for nitrile